2017
DOI: 10.1002/glia.23279
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive downregulation protein kinase C epsilon in hSOD1G93A astrocytes influences mGluR5 signaling and the regulation of glutamate uptake

Abstract: Accumulating evidence indicates that motor neuron degeneration in amyotrophic lateral sclerosis (ALS) is a non-cell-autonomous process and that impaired glutamate clearance by astrocytes, leading to excitotoxicity, could participate in progression of the disease. In astrocytes derived from an animal model of ALS (hSOD1 rats), activation of type 5 metabotropic glutamate receptor (mGluR5) fails to increase glutamate uptake, impeding a putative dynamic neuroprotective mechanism involving astrocytes. Using astrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 66 publications
(116 reference statements)
0
14
0
Order By: Relevance
“…Moreover, recent in vivo work from our group showed that constitutive genetic ablation of mGlu 5 receptors in the SOD1 G93A mouse significantly increased survival probability and slowed the progression of the pathology (Bonifacino et al, 2017 ; Bonifacino, Provenzano, et al, 2019 ). Also there are several reports of mGlu5 receptors affecting a variety of cellular processes in ALS (Anneser et al, 1999 ; Brownell et al, 2015 ; Rossi et al, 2008 ; Vergouts et al, 2018 ; Vermeiren et al, 2006 ). Thus, considering their pleiotropic characteristics, mGlu 5 receptors represent a promising and potential druggable target in CNS diseases (Ribeiro et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent in vivo work from our group showed that constitutive genetic ablation of mGlu 5 receptors in the SOD1 G93A mouse significantly increased survival probability and slowed the progression of the pathology (Bonifacino et al, 2017 ; Bonifacino, Provenzano, et al, 2019 ). Also there are several reports of mGlu5 receptors affecting a variety of cellular processes in ALS (Anneser et al, 1999 ; Brownell et al, 2015 ; Rossi et al, 2008 ; Vergouts et al, 2018 ; Vermeiren et al, 2006 ). Thus, considering their pleiotropic characteristics, mGlu 5 receptors represent a promising and potential druggable target in CNS diseases (Ribeiro et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of Group I mGluRs on hSOD1 G93A astrocytes results in the death of these cells and this effect is blocked with an mGluR5 antagonist [108]. Moreover, while wild-type astrocytes treated with a Group I agonist enhances aspartate uptake, astrocytes derived from hSOD1 G93A rats fail to increase aspartate uptake, indicating that the mutant gene blocks protective roles of the Group I agonist [81,109]. Proper removal of excitatory transmitters such as aspartate and glutamate can be important in preventing excitotoxicity in diseases such as ALS, where increased glutamate levels and reduced glutamate transporter expression is evident in tissue from ALS patients [110,111].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Group I metabotropic glutamate receptors (mGluR1 and mGluR5) are actively involved in the regulation of important cellular processes altered in ALS and play a key role in the complex ALS scenario [44,45,46,47,48,49,50]. Starting from our previous results showing that mGluR1 and mGluR5 abnormally increase the release of glutamate in the spinal cord of late symptomatic SOD1 G93A mice [26], we here investigated the expression and function of these receptors during disease progression to unveil whether they can also modify glutamate transmission at more precocious stages of the disease.…”
Section: Discussionmentioning
confidence: 99%